Barriers, Attitudes, And Self-Efficacy Of People With Disabilities In Recreational Sports Activities Participation In Saudi Arabia - Salawi, Abdulelah Ahmad (2014)
This study investigates factors that predict participation of people with disabilities in recreational sports. Kajian ini menyiasat faktor-faktor yang meramalkan penyertaan orang kurang upaya dalam sukan rekreasi